Long-term increases in tree water-use efficiency across China are associated with CO2 and hydroclimatic variation - Yali Ding; Li Wen; Jingzhi Zhang; Wei Zhang; Hongsong Chen; Shanshan Song; Zongrui Lai; Jinxing Zhou; Guanghui Lin (Journal of Hydrology, 2026)

Occurrence, spatiotemporal variation, source, and risk of organophosphate triesters and diesters in soil of e-waste dismantling parks - Wenya Yang; Feng Zhang; Qiubing Ma; Xuwenqi Zhang; Minmin Hou; Xiaoling Jin; Feihang Xu; Jie Lin; Pengfei Li; Baofeng Zhang; Yali Shi; Yaqi Cai (Environmental Research, 2026)

Biodegradable mulching and nitrogen fertilization differentially affect AM fungal community structure and functioning in a semi-arid maize agroecosystem - Lin Mao; Yae Luo; Jingru Yan; Huan Jin; Dachuan Liu; Jiayao Han; Yali Zhang; Zhou Fang; He Mao (Mycorrhiza, 2026)

Agricultural management shapes soil multitrophic communities and biodiversity-ecosystem function relationships in a dryland agroecosystem - Jiayao Han; Yali Zhang; Hao Xi; Lin Mao; Zhou Fang; Chenyu Li; Yongjun Liu (Agriculture, Ecosystems & Environment, 2026)

Phenotypic and molecular characterization of Vibrio cholerae from aquatic products - Yao Shen; Jiangang Ma; Huafeng Jian; Shuaijie Song; Zhiyu Li; Fengcheng Miao; Xiaoqian Long; Yukun Jie; Yuchen Wang; Feng Lin; Yali Dang; Hua Yang (Journal of Invertebrate Pathology, 2026)

Microbial-mediated soil carbon accrual under 12-year reduced nitrogen fertilisation and intercropping - Kepan Yang; Yali Liu; Chaoqun Zou; Jianghao Tan; Huiying Lin; Lei Liu; Xiting Zhang; Enqing Hou (Agriculture, Ecosystems & Environment, 2026)

Improving high-degree-polymerization GOS synthesis of a marine cold-active β-galactosidase via semi-rational design - Lin Pan; Yali Zhang; Zhe Wang; Chenxu Fan; Qionghui You; Jiahong Wu; Fangqi Feng; Xiaohui Wang (Archives of Microbiology, 2026)

Socioeconomic drivers of riverine biochemical oxygen demand: Insights from interpretable machine learning - Na Huang; Dawei Wang; Penghui Li; Lin Chen; Wei Wang; Zeng Zhou; Pei Xu; Sile Li; Yali Zhang; Yilan Jiang (Journal of Environmental Management, 2026)

A new method for mangrove biomass prediction based on automatic machine learning and multi-source UAV data fusion - Yutong Xie; Yichao Tian; Qiang Zhang; Yali Zhang; Jin Tao; Junliang Lin; Mohd Hasmadi Ismail; Pakhrizad Bin Hassan Zaki; Weirong Qin (International Journal of Remote Sensing, 2026)

Corrigendum to “Phenotypic and molecular characterization of vibrio cholerae from aquatic products” [J. Invertebr. Pathol. 218 (2026) 108644] - Yao Shen; Jiangang Ma; Huafeng Jian; Shuaijie Song; Zhiyu Li; Fengcheng Miao; Xiaoqian Long; Yukun Jie; Yuchen Wang; Feng Lin; Yali Dang; Hua Yang (Journal of Invertebrate Pathology, 2026)

Enhanced per- and polyfluoroalkyl substances (PFAS) exposure in a large estuary-coastal sea continuum shortly after a spring flood event - Yali Li; Chunhui Wang; Tian Lin; Yicheng Li; Yongxin Mai; Junjie Wang; Jiawen Yuan; Cuizhi Sun; Jialu Wang; Xiyang Zhang; Weidong Zhai (Water Research, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Source apportionment and source-to-sink relationship of PAHs in surface sediments of complex estuarine environment - Jiawen Yuan; Yali Li; Xinyi Liu; Chongtai Chen; Yongxin Mai; Tian Lin (Applied Geochemistry, 2026)

Influence of salinity on the dynamic improving nutritional value of channel catfish (Ictalurus punctatus): Insights from targeted and untargeted metabolomics and antioxidant capacity analysis - Zhen Li; Yali Yu; Quanyou Guo; Na Lin; Xiaorong Lu; Jie Peng; Tao Mao; Yuntao Zhou; Lang Zhang; Liu Fang (Aquaculture, 2026)

Boosting multi-heavy metal sequestration in king grass: Unveiling the role of Serendipita indica symbiosis and the key root exudate GABA - Yali Duan; Jialiang Luo; Miaomiao Wang; Dong Li; Huiping Feng; Li Lin; Qianli An; Shunqing Xu; Zhiqiang Zhu (Journal of Environmental Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

TLR5-mediated pathogenic bacteria defense and functional maintenance of Misgurnus anguillicaudatus ovary - Yali Wang; Mengzhen Wang; Yanxia Lin; Yunfan Han; Enping Chen; Xiaohua Xia (Aquaculture, 2026)

Chicken sternum cartilage protein-chelated calcium: enhance bone density in vivo and in vitro, with insights into chelation mechanism - Shikun Suo; Yanli Wang; Lihui Du; Maolin Tu; Kuo Dang; Jingyi Chen; Yi Lin; Yali Dang; Qingqing Li (Food Research International, 2026)

Cadmium exposure is associated with impaired ovarian function: Potential role of cadmium-induced ferroptosis in granulosa cells - Jing Li; Yutong Wang; Yali Huang; Nidong Li; Yingxin Zhu; Shengli Lin; Linlin Wang; Wei Guo; Lailai Yan; Chan Tian; Ying Wang (Journal of Hazardous Materials, 2026)

Colorimetric sensor array enabled by deep eutectic solvent-regulated anthocyanins and electrospun polylactic acid nanofiber for pork freshness monitoring - Yali Zhao; Xinlei Wang; Kai Wen Choo; Mengshi Lin; Farhana R. Pinu; Yunfei Xie; Zhilong Yu (Food Chemistry, 2025)

Diterpenoids from Euphorbia lathyris L.: a comprehensive review update - Xiuli Wang; Yang Xu; Yali Wang; Fei Lin; Hua Li; Lixia Chen (Phytochemistry Reviews, 2025)

Occurrence, spatial distribution, and risk assessment of per- and polyfluoroalkyl substances in soil and groundwater of a petrochemical industrial park in China - Qitao Lei; Lin Niu; Zhi Tang; Yali Shi; Xiaoli Zhao; Yaqi Cai (Environmental Pollution, 2025)

Synthesis of N-acyl-homoserine lactones analogs for improving the potential application of Acidithiobacillus thiooxidans in bioleaching - Deping Tang; Mengjiao Li; Wentao Song; Yanpeng Xi; Yali Liu; Yanyan Lin; Hao Feng; Aihong Mao (Archives of Microbiology, 2025)

Multiple light sources excited fluorescence image-based non-destructive method for citrus Huanglongbing disease detection - Kangting Yan; Xipeng Fang; Weiguang Yang; Xidan Xu; Shaozhen Lin; Yali Zhang; Yubin Lan (Computers and Electronics in Agriculture, 2025)

Orientation construction and comparison of mercury removal sites by physical and chemical adsorption on cotton stalk biochar - Guoliang Li; Shuxiao Wang; Qingru Wu; Tao Yue; Jiajia Gao; Yali Tong; Mingyu Zhang; Lin Zhang; Chenyang Zhang; Sizhe Xie (Fuel, 2025)

Trade-off/Synergy Relationship and Time-lag Effect of Ecosystem Services in the Peak-cluster Depression Basins on the Sino-Vietnamese Border in China - Donghua Wang; Yichao Tian; Yali Zhang; Qiang Zhang; Liangliang Huang; Jin Tao; Junliang Lin (Chinese Geographical Science, 2025)

Non-destructive prediction of soluble solids content and firmness and maturity determination of guava fruit using color and fluorescence imaging - Shaozhen Lin; Kangting Yan; Zhilei Sun; Zhijie Zhang; Yubin Lan; Linlin Wang; Yali Zhang (Postharvest Biology and Technology, 2025)

Copper selenide enhanced magnetic biochar for elemental mercury removal from coal combustion flue gas - Lin Zhang; Yang Zheng; Guoliang Li; Jiajia Gao; Yali Tong; Tao Yue (Journal of Environmental Sciences, 2025)

Genomic insights into the brooding reproduction and climate-driven dynamics of Pocillopora damicornis in the Anthropocene - Jie Li; Yali Liu; Zhixin Zhang; Yu Chen; Jian Zhang; Haiyan Yu; Yingyi Zhang; Cong Liu; Zhuang Shao; David G. Bourne; Meng Qu; Si Zhang; et al. (Science China Life Sciences, 2025)

Ecological connectivity between mangroves and seagrasses increases sediment blue carbon storage - Xinao Guo; Shanshan Song; Lieyi Chen; Conghe Zhang; Shengbin Ye; Yali Ding; Ruikun Gou; Xiaoping Huang; Shuguo Lv; Neil Saintilan; Daniel A. Friess; Guanghui Lin (Estuarine, Coastal and Shelf Science, 2025)

MCPA-Na exposure in aquatic systems: disruption of pathways and increased susceptibility to infection in fish - Yanxia Lin; Ran Shi; Mengzhen Wang; Yali Wang; Yunfan Han; Yongcui Ma; Liyin Li; Xiaohua Xia (Aquatic Toxicology, 2025)

Topping-induced transcriptome changes reveal PaSPL-mediated regulation of plant architecture in Platanus acerifolia - Yanping Zhang; Yali Guan; Yongkang Lu; Lin Wang; Yuqing Chen; Manzhu Bao (Plant Molecular Biology, 2025)

Salicylic Acid Alleviates Cold Stress in Rice via Regulating Nutrient Absorption, Osmotic Material Content, Antioxidation System, and Expression of Cold Tolerance Genes - Qingshan Xu; Yulian Yan; Qianqian Wei; Hangfeng Wang; Chunxin Chi; Lin Pan; Yali Kong; Lianfeng Zhu; Wenhao Tian; Junhua Zhang; Chunquan Zhu (Journal of Plant Growth Regulation, 2025)

Hand preferences in captive non-human primates are associated with generation and stress level - Lin Wang; Yunchao Luo; Haoyu Sun; Yiru Gu; Yu Wang; Yali Bai; Zhongqiu Li (Applied Animal Behaviour Science, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

Differential microbial degradation of cross-linked Polythene by Aspergillus niger in space and on the ground - Shuyuan Zhang; Lei Dang; Weiliang Li; Qin Zhang; Kui Xiao; Tong Tong; Qianqian Liu; Lingling Ma; Nana Chen; Lantao Zhang; Yali Feng; Yan Song; et al. (Chemical Engineering Journal, 2025)

Antibacterial mechanisms of PLA on Aeromonas hydrophila and its application in fish disease resistance and fish preservation - Xiaohua Xia; Yanxia Lin; Yali Wang; Lu Qin; Shuang Liu; Hongwei Zhang; Xiaowen Zhang; Yi Li (Food Bioscience, 2025)

Reproductive toxicity and molecular mechanisms of benzo[a]pyrene exposure on ovary, testis, and brood pouch of sex-role-reversed seahorses (Hippocampus erectus) - Yuanyuan Xue; Fang Wang; Xiaolei Su; Mingzhu Li; Hansheng Yan; Shiyi Zheng; Yicong Ma; Jie Dong; Yali Liu; Qiang Lin; Kai Wang (Environmental Pollution, 2025)

Modification of microporous bionanocomposite films with visible light-activated photocatalytic antimicrobial TNT-CuO nanoparticles for active fruit packaging - Huan Zhang; Shuting Huang; Yali Zhao; Hong Sabrina Tian; Mengshi Lin; Yunfei Xie; Zhilong Yu (Food Research International, 2025)

On the multiscale processes leading to three heavy rainfall episodes over beijing and its periphery in july 2016 - Rudi Xia; Chong Wu; Da-Lin Zhang; Yali Luo; Jinfang Yin (Meteorology and Atmospheric Physics, 2025)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

Drivers of denitrification and nitrification in a dryland agroecosystem: The role of abiotic and biotic factors - Zhou Fang; Zhenling Peng; Yali Zhang; Jiayao Han; Jianbin Pan; Qi Zhang; Lin Mao; Guoxi Shi; Yongjun Liu; Huyuan Feng; Xavier Le Roux (Applied Soil Ecology, 2024)

Remote sensing inversion of suspended particulate matter in the estuary of the Pinglu Canal in China based on machine learning algorithms - Jinying Mo; Yichao Tian; Jiale Wang; Qiang Zhang; Yali Zhang; Jin Tao; Junliang Lin (Frontiers in Marine Science, 2024)
Introduction Suspended particulate matter (SPM) is a critical indicator of water quality and has a significant impact on the nearshore ecological environment. Consequently, the quantitative evaluation of SPM concentrations is essential for managing nearshore environments and planning marine resources. Methods This study utilized Sentinel-2’s single band and water index variables to develop a remote sensing inversion model for oceanic SPM in the estuary of the Pinglu Canal in China. Six machine learning algorithms were employed: K-nearest neighbor regression (KNNR), AdaBoost regression (ABR), random forest (RF), gradient boosting regression (GBR), extreme gradient boosting regression (XGBR), and light generalized boosted regression (LGBM). The model with the optimal performance was then selected for further analysis. This research applied the established model to investigate the spatial-temporal dynamics of SPM from 2021 to 2023. Results The findings indicated that (1) the XGBR algorithm exhibited superior performance (R 2 = 0.9042, RMSE = 3.0258 mg/L), with LGBM (R 2 =0.8258, RMSE = 4.0813 mg/L) and GBR (R 2 = 0.823, RMSE = 4.3477 mg/L) also demonstrating effective fitting. However, the ABR, RF, and KNNR algorithms produced less satisfactory fitting results. (2) Additionally, the study revealed that the combination of input variables in the XGBR algorithm was more accurate than single-variable inputs. (3) The contribution of single-band variables to the XGBR algorithm surpassed that of water index variables, with B12, B4, and B11 emerging as the top three influential variables in the model. (4) The annual SPM concentration in the study area exhibited an overall increasing trend, while its spatial distribution generally decreased from the estuary toward the Maowei Sea and Qinzhou Bay. Discussion The combination of Sentinel-2 data and XGBR model has shown good performance in retrieving SPM concentration, providing a new method and approach for large-scale estimation of SPM concentration.

Dissection of molecular mechanisms of liver injury induced by microcystin-leucine arginine via single-cell RNA-sequencing - Yunmeng Bai; Yali Song; Miaoran Li; Jinhuan Ou; Hong Hu; Nan Xu; Min Cao; Siyu Wang; Lin Chen; Guangqing Cheng; Zhijie Li; Gang Liu; et al. (Journal of Environmental Sciences, 2024)

Matching and driving mechanism analysis of the supply and demand relationships of soil conservation services in karst peak-cluster depression basin in Southwest Guangxi, China - Jianwei Li; Yichao Tian; Donghua Wang; Qiang Zhang; Jin Tao; Yali Zhang; Junliang lin (CATENA, 2024)

Correction: Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2024)

The detoxification ability of sex-role reversed seahorses determines the sexual dimorphism in immune responses to benzo[a]pyrene exposure - Kai Wang; Yuanyuan Xue; Yali Liu; Xiaolei Su; Lei Wei; Chunhui Lv; Xu Zhang; Lele Zhang; Longwu Jia; Shiyi Zheng; Yicong Ma; Hansheng Yan; et al. (Science of The Total Environment, 2024)

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

LINC00460 promotes neuroblastoma tumorigenesis and cisplatin resistance by targeting miR-149-5p/DLL1 axis and activating Notch pathway in vitro and in vivo - Yali Xu; Zhixin Qiu; Jinwen Chen; Lihong Huang; Jiaqi Zhang; Junshan Lin (Drug Delivery and Translational Research, 2024)

Study on biodegradation of polyurethane coating on PCB by Aspergillus brasiliensis in space - Qianqian Liu; Wende Zhang; Junxia Yuan; Nana Chen; Qin Zhang; Yali Feng; Jinlu Yang; Lin Lu; Xunfeng Zhao; Chaofang Dong; Hong Yin; Kui Xiao (Chemical Engineering Journal, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Effects of significant emission changes on PM2.5 chemical composition and optical properties from 2019 to 2021 in a typical industrial city of eastern China - Xiangpeng Huang; Changping Li; Chao Pan; Yue'e Li; Wei Zheng; Guangwu Lin; Haiwei Li; Yunjiang Zhang; Junfeng Wang; Yali Lei; Jianhuai Ye; Xinlei Ge; et al. (Atmospheric Research, 2024)

Characterizing sedimentary black carbon in the Pearl River Estuary, Southern China - Xinyi Liu; Yali Li; Tian Lin; Nairong Guo; Jiawen Yuan; Ying Yang; Wei-dong Zhai (Marine Chemistry, 2024)

Slc43a2+ T cell metastasis from spleen to brain in RGNNV infected teleost - Qing Wang; Yali Liu; Minlin Zhang; Min Yang; Jiantao Liang; Xiaoling Zuo; Shaowen Wang; Xianze Jia; Huihong Zhao; Han Jiang; Qiang Lin; Qiwei Qin (Science China Life Sciences, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

Key decomposers of straw depending on tillage and fertilization - Hao Xi; Mengying Jia; Yakov Kuzyakov; Zhenling Peng; Yali Zhang; Jiayao Han; Gohar Ali; Lin Mao; Jianjun Zhang; Tinglu Fan; Yongjun Liu (Agriculture, Ecosystems & Environment, 2023)

Evolutionary traits and functional roles of chemokines and their receptors in the male pregnancy of the Syngnathidae - Han Jiang; Zhanwei Zhao; Haiyan Yu; Qiang Lin; Yali Liu (Marine Life Science & Technology, 2023)

Assessing the potential risks, sources and the relationship between the dissolved and particulate polycyclic aromatic hydrocarbons (PAHs) in the typical semi-enclosed bay, Bohai Bay of China - Kun Lin; Rui Wang; Liju Tan; Shan Jiang; Hongyan Xu; Yali Cao; Jiangtao Wang (Marine Environmental Research, 2023)

Interactions between flue gas desulfurization gypsum and biochar on water infiltration characteristics and physicochemical properties of saline-alkaline soil - Peijun Wang; Xiaolan Lin; Qi Liu; Ziqi Lin; Yali Yang; Hui Chen; Shenglong Fan (Environmental Monitoring and Assessment, 2023)
The application of flue gas desulfurization gypsum (FGDG) improves the soil structure, reduces soil pH, and accelerates soil salt leaching. Biochar amendment to soil can affect the soil infiltration rate, increase soil porosity, decrease soil bulk density, and enhance the water retention capacity. This study investigated the interactive effect of FGDG and biochar on water infiltration characteristics and physicochemical properties as well as determined the optimal amendment rate as a saline-alkaline soil conditioner. Seven experimental schemes were designed, and the newly reclaimed cultivated soil from Pingtan Comprehensive Experimental Zone in Fujian Province, China, was used in an indoor soil column experiment to simulate soil infiltration. Five models were employed to describe the infiltration process. The power function was used to represent the dynamic process of the wetting front. The conclusions of this study are as follows: (1) there was a reduction in the infiltration capacity of saline-alkaline soil (sandy soil) in each treatment, and the application of FGDG alone had the highest inhibition effect compared to the control (CK). The Kostiakov model provides the best fit for the experimental data of soil cumulative infiltration. (2) All treatments increased the total porosity and water content of saline-alkali soil, with the combined application of FGDG and biochar found to be more effective. (3) The application of FGDG alone or in combination with biochar decreased the pH and increased the electrical conductivity of the saline-alkali soil significantly, with the combined application having the most significant effect. In contrast, soil amended with biochar alone had minimal effect on the pH and EC of the soil. (4) The best improvement ratio was achieved with the F1B2 combination (75 g/kg FGDG + 30 g/kg biochar).

Multi-scale domain and microstructure engineering for the high-energy-storage BCZT based lead-free relaxor ferroelectric ceramics - Jiayue Song; Fei Yan; Jinfeng Lin; Guanglong Ge; Cheng Shi; Jin Qian; Yali Hao; Yongqi Wei; Wu Yao (Chemical Engineering Journal, 2023)

A novel noninvasive brain–computer interface by imagining isometric force levels - Li Hualiang; Ye Xupeng; Liu Yuzhong; Xie Tingjun; Tan Wei; Shen Yali; Wang Qiru; Xiong Chaolin; Wang Yu; Lin Weilin; Jinyi Long (Cognitive Neurodynamics, 2023)

Ent-kauranes and ent-atisanes from Euphorbia wallichii and their anti-inflammatory activity - Yali Wang; Qinghua Jiang; Dejuan Sun; Na Zhang; Yu Lin; Hua Li; Lixia Chen (Phytochemistry, 2023)

The large decline in carbonate δ238U from a PETM section at Tingri (South Tibet) was driven by local sea-level changes, not global oceanic anoxia - Qinghai Zhang; Lin Ding; Xinming Chen; Gregory A. Brennecka; Yali Sun; Xuesong Ma; Bintao Gao; Qian Zhang; Helmut Willems (Earth and Planetary Science Letters, 2023)

The genetic basis of the leafy seadragon’s unique camouflage morphology and avenues for its efficient conservation derived from habitat modeling - Meng Qu; Yingyi Zhang; Zexia Gao; Zhixin Zhang; Yali Liu; Shiming Wan; Xin Wang; Haiyan Yu; Huixian Zhang; Yuhong Liu; Ralf Schneider; Axel Meyer; et al. (Science China Life Sciences, 2023)

Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2023)
Immunophenotyping is proving crucial to understanding the role of the immune system in health and disease. High-throughput flow cytometry has been used extensively to reveal changes in immune cell composition and function at the single-cell level. Here, we describe six optimized 11-color flow cytometry panels for deep immunophenotyping of human whole blood. A total of 51 surface antibodies, which are readily available and validated, were selected to identify the key immune cell populations and evaluate their functional state in a single assay. The gating strategies for effective flow cytometry data analysis are included in the protocol. To ensure data reproducibility, we provide detailed procedures in three parts, including (1) instrument characterization and detector gain optimization, (2) antibody titration and sample staining, and (3) data acquisition and quality checks. This standardized approach has been applied to a variety of donors for a better understanding of the complexity of the human immune system.

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

Evolvement of carbamazepine under solar irradiation in the presence of chlorine: Efficiency, influences, degradation pathways and ecotoxicity - Haixiang Jia; Xiaoyan Y. Ma; Yu Lin; Shengjiong Yang; Yali An; Yihan Chen; Xiaochang C. Wang (Chemical Engineering Journal, 2023)

Prognostic and functional roles of EIF4G1 in lung squamous cell carcinoma - Baoxin Bai; Lin Dong; Minghao Feng; Zhiwen Zhang; Ying Lu; Zengguang Xu; Yali Liu (Human Cell, 2023)
Eukaryotic translation initiation factor 4 gamma 1 (EIF4G1) is highly expressed in many cancers and affects their occurrence and development. However, the effect of EIF4G1 on the prognosis, biological function and the relevant mechanism in lung squamous cell carcinoma (LSCC) is unclear. Through clinical cases, Cox’s proportional hazard model and Kaplan–Meier plotter survival analysis, we find the expression levels of EIF4G1 are dependent on age and clinical stage, high expression of EIF4G1 could be used to predict the overall survival of LSCC patients. LSCC cell line NCI-H1703, NCI-H226 and SK-MES-1infected with EIF4G1 siRNA are used to detect the function of EIF4G1 with cell proliferation and tumorigenesis in vivo and vitro. The data show that EIF4G1 promotes tumor cell proliferation and the G1/S transition of cell cycle in LSCC, then the biological function of LSCC is effected by the AKT/mTOR pathway. Above all, these results have demonstrated that EIF4G1 promotes LSCC cell proliferation and may represent an indicator of prognosis in LSCC.

Identification of a 17β-estradiol-degrading Microbacterium hominis SJTG1 with high adaptability and characterization of the genes for estrogen degradation - Weiliang Xiong; Wanli Peng; Yali Fu; Zixin Deng; Shuangjun Lin; Rubing Liang (Journal of Hazardous Materials, 2023)

Evaluation and Quantitative Attribution Analysis of Water Yield Services in the Peak-cluster Depression Basins in Southwest of Guangxi, China - Donghua Wang; Yichao Tian; Yali Zhang; Liangliang Huang; Jin Tao; Yongwei Yang; Junliang Lin; Qiang Zhang (Chinese Geographical Science, 2023)

Mechanism of simultaneous lead and chromium removal from contaminated wastewater by a schwertmannite-like mineral - Mingyan Shi; Yali Zhang; Weibin Hong; Jiayu Liu; Huijie Zhu; Xu Liu; Yuxin Geng; Zhenyin Cai; Shaonan Lin; Chengzhi Ni (Environmental Science and Pollution Research, 2022)

Rare earth element characteristics of the Permian Lucaogou Formation shale in the Junggar Basin, Northwest China - Jun Yin; Li Wang; Haitao Lin; Yali Zhu (Arabian Journal of Geosciences, 2022)

On the Diurnal Cycle of Heavy Rainfall over the Sichuan Basin during 10–18 August 2020 - Rudi Xia; Yali Luo; Da-Lin Zhang; Mingxin Li; Xinghua Bao; Jisong Sun (Advances in Atmospheric Sciences, 2021)
A sustained heavy rainfall event occurred over the Sichuan basin in southwest China during 10–18 August 2020, showing pronounced diurnal rainfall variations with nighttime peak and afternoon minimum values, except on the first day. Results show that the westward extension of the anomalously strong western Pacific subtropical high was conducive to the maintenance of a southerly low-level jet (LLJ) in and to the southeast of the basin, which favored continuous water vapor transport and abnormally high precipitable water in the basin. The diurnal cycle of rainfall over the basin was closely related to the periodic oscillation of the LLJ in both wind speed and direction that was caused by the combination of inertial oscillation and terrain thermal forcing. The nocturnally enhanced rainfall was produced by moist convection mostly initiated during the evening hours over the southwest part of the basin where high convective available potential energy with moister near-surface moist air was present. The convective initiation took place as cold air from either previous precipitating clouds from the western Sichuan Plateau or a larger-scale northerly flow met a warm and humid current from the south. It was the slantwise lifting of the warm, moist airflow above the cold air, often facilitated by southwest vortices and quasi-geostrophic ascent, that released the convective instability and produced heavy rainfall.

Carbon transfer from the submerged macrophyte Hydrilla verticillata to zooplankton: a 13C-labeled mesocosm study - Ling Su; Zongan Jin; Lichao Xie; Yali Tang; Zhengwen Liu; Ping Zhong; Yaling Su; Qiuqi Lin (Hydrobiologia, 2021)

Cornel iridoid glycoside induces autophagy to protect against tau oligomer neurotoxicity induced by the activation of glycogen synthase kinase-3β - Cuicui Yang; Xuelian Li; Li Zhang; Yali Li; Lin Li; Lan Zhang (Journal of Natural Medicines, 2019)

Island soil quality assessment and the relationship between soil quality and land-use type/topography - Xia Lu; Yuanzhi Zhang; Yali Lin; Sen Zhang; Qian Zhao (Environmental Monitoring and Assessment, 2019)

Structural predication and antigenic analysis of Toxoplasma gondii ROP20 - Jian Zhou; Wanchun Wang; Pengxia Song; Lin Wang; Yali Han; Jingjing Guo; Zhen Hao; Xi Zhu; Qiong Zhou; Xiadong Du; Gang Lu; Shenyi He; et al. (Acta Parasitologica, 2018)
Toxoplasma gondii infects almost all the warm-blooded animals. ROP20 protein is expressed in the rhoptry of Toxoplasma gondii . In this study, the secondary structure of ROP20 was analyzed using SMART software. We constructed and analyzed the 3D model of ROP20 protein using SWISS-MODEL online procedure and Visual Molecular Dynamics (VMD) software. The structure analysis fully indicated that ROP20 protein is an important member of the ROP family. Furthermore, We used DNASTAR software and Epitope Database online service to analyze liner-B cell epitopes and T-cell epitopes of ROP20 protein. All the analysis results of ROP20 protein can provide positive information on treatment and vaccine for toxoplasmosis. Moreover, ROP20 gene was obtained from PCR, and a recombinant eukaryotic expression vector (pEGFP-C1-ROP20) was constructed in the following study. After restriction enzyme digestion, the constructed plasmid was transfected into HEK 293-T cells. The RT-PCR result indicated that the recombinant plasmid could transcribe successfully in HEK 293-T cell. The results of western blotting indicated the expressed proteins can be recognized by anti-STAg mouse sera.

Auxin is Involved in Lateral Root Formation Induced by Drought Stress in Tobacco Seedlings - Chengdong Wang; Yang Zhao; Pengyuan Gu; Fuyu Zou; Lin Meng; Wenjing Song; Yinju Yang; Shusheng Wang; Yali Zhang (Journal of Plant Growth Regulation, 2018)

Differential Response of First-Order Lateral Root Elongation to Low Potassium Involves Nitric Oxide in Two Tobacco Cultivars - Wenjing Song; Ren Xue; Yao Song; Yang Bi; Zhihao Liang; Lin Meng; Caixia Dong; Chengdong Wang; Guangliang Liu; Jianxin Dong; Yali Zhang (Journal of Plant Growth Regulation, 2018)

Relationship between landslides and active normal faulting in the epicentral area of the AD 1556 M~8.5 Huaxian Earthquake, SE Weihe Graben (Central China) - Gang Rao; Yali Cheng; Aiming Lin; Bing Yan (Journal of Earth Science, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

A novel method to harvest Chlorella sp. by co-flocculation/air flotation - Haiyang Zhang; Zhe Lin; Daoyong Tan; Chunhua Liu; Yali Kuang; Zhu Li (Biotechnology Letters, 2017)

Ground-based radar reflectivity mosaic of mei-yu precipitation systems over the Yangtze River–Huaihe River basins - Yali Luo; Weimiao Qian; Yu Gong; Hongyan Wang; Da-Lin Zhang (Advances in Atmospheric Sciences, 2016)

Potassium deficiency inhibits lateral root development in tobacco seedlings by changing auxin distribution - Wenjing Song; Shangjun Liu; Lin Meng; Ren Xue; Chengdong Wang; Guangliang Liu; Caixia Dong; Shusheng Wang; Jianxin Dong; Yali Zhang (Plant and Soil, 2015)

Light Quality Regulates Lateral Root Development in Tobacco Seedlings by Shifting Auxin Distributions - Lin Meng; Wenjing Song; Shangjun Liu; Jianxin Dong; Yali Zhang; Chengdong Wang; Yimin Xu; Shusheng Wang (Journal of Plant Growth Regulation, 2015)

Systemic Review of Published Reports on Primary Cutaneous Cryptococcosis in Immunocompetent Patients - Lin Du; Yali Yang; Julin Gu; Jianghan Chen; Wanqing Liao; Yuanjie Zhu (Mycopathologia, 2015)

A review of seasonal climate prediction research in China - Huijun Wang; Ke Fan; Jianqi Sun; Shuanglin Li; Zhaohui Lin; Guangqing Zhou; Lijuan Chen; Xianmei Lang; Fang Li; Yali Zhu; Hong Chen; Fei Zheng (Advances in Atmospheric Sciences, 2015)

Cryptococcal Meningitis in Patients with Autoimmune Hemolytic Anemia - YaLi Yang; Junjun Sang; Weihua Pan; Lin Du; Wanqing Liao; Jianghan Chen; Yuanjie Zhu (Mycopathologia, 2014)

Identification of a novel mutation of the gene for gap junction protein α3 (GJA3) in a Chinese family with congenital cataract - Ying Hu; Lin Gao; Yali Feng; Tao Yang; Shangzhi Huang; Zhengbo Shao; Huiping Yuan (Molecular Biology Reports, 2014)

Perfluorinated Compounds in Surface Water and Organisms from Baiyangdian Lake in North China: Source Profiles, Bioaccumulation and Potential Risk - Zhen Zhou; Yali Shi; Wenhui Li; Lin Xu; Yaqi Cai (Bulletin of Environmental Contamination and Toxicology, 2012)